2022
DOI: 10.2144/fsoa-2022-0052
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of Oxidized HMGB1 As a Mediator and Biomarker

Abstract: HMGB1 is a dual-function protein that acts as a chromatin-binding protein and as a danger-associated molecular pattern (DAMP) when released from activated immune cells or injured tissue. In much of the HMGB1 literature, immunomodulatory effects of extracellular HMGB1 are proposed to depend on its oxidation state. However, many of the foundational studies for this model have been retracted or flagged with expressions of concern. The literature on HMGB1 oxidation reveals a diversity of redox proteoforms of HMGB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…Using this approach, we were unable to detect acetylation on K-3, K-7, or K-12 residues using a highly specific nanoLC-PRM/HRMS method ( Scheme 1 ). There is also substantial evidence suggesting that HMGB1 NLS1 and NLS2 acetylation is required to facilitate its secretion [ 31 , 32 , 41 , 61 ], although many of the key studies have been retracted or statements of concern issued [ 28 ]. Consequently, it is perhaps not surprising that we were unable to detect any acetylated forms of HMGB1 secreted after treatment of A549 lung cells with cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this approach, we were unable to detect acetylation on K-3, K-7, or K-12 residues using a highly specific nanoLC-PRM/HRMS method ( Scheme 1 ). There is also substantial evidence suggesting that HMGB1 NLS1 and NLS2 acetylation is required to facilitate its secretion [ 31 , 32 , 41 , 61 ], although many of the key studies have been retracted or statements of concern issued [ 28 ]. Consequently, it is perhaps not surprising that we were unable to detect any acetylated forms of HMGB1 secreted after treatment of A549 lung cells with cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 secretion during the treatment of NSCLC has been reported, although the studies were flawed by the analysis of HMGB1 in serum instead of plasma [ 26 , 27 ]. Regrettably, a significant number of studies of HMGB1 secretion have been conducted using serum instead of plasma [ 28 ] Our study utilizing matched plasma and serum samples from twenty healthy control subjects revealed that HMGB1 is released when blood is allowed to clot and form serum [ 15 ]. The process of clotting led to a substantial 30-fold increase in HMGB1 concentrations, escalating from 0.2 ng/mL in plasma to 6 ng/mL in serum [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as TMJ disorders involving traumatic synovitis are usually promoted by sterile inflammation, the biomarkers identified should be similar. 52,53 As targeted biologics, such as anti-HMGB1-mc/pc AB, are being developed to antagonize the actions of proinflammatory cytokines, there is a need to improve these compounds' pharmacokinetics and half-life. To this end, a myriad of drug delivery vehicles are being developed to circumvent the harsh environment that exists in the oral facial area for biotherapeutics.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…However, as TMJ disorders involving traumatic synovitis are usually promoted by sterile inflammation, the biomarkers identified should be similar. 52,53…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%